Henneguya schizodon n. sp. (Myxozoa, Myxobolidae), a parasite of the Amazonian teleost fish Schizodon fasciatus (Characiformes, Anostomidae) - Eiras, Jorge Costa (2004)
A new histozoic species of myxosporean [Henneguya schizodon n. sp.) is described from the Amazon River teleost fish Schizodon fasciatus Spix & Agassiz, 1 892 [Characiformes, Anostomidae). The plasmodia, which showed asynchronous development, were located in the kidney of the host. The spore body was ellipsoidal and was 13.1 (12-14) μm long by 3.3 (3-4) μm wide. The total length of the spore was 28.9 (27-30) μm, and each valve had a caudal process measuring 16.3 (15-17) μm. The polar capsules were 5.4 (5-0) μm long by 1.3 (1-1.5) μm wide, and each had a polar filament with 8-10 coils. The characteristics of the species were compared with nearly all the species described so far, including all the species reported from South American fishes. This comparison allows to consider the material as a new species, and the name Henneguya schizodon n. sp. is proposed.